Language, culture, and society an introduction to linguistic anthropology - Salzmann, Zdene?k; Stanlaw, James; Adachi, Nobuko (2018)
"Why should we study language? How do the ways in which we communicate define our identities? And how is this all changing in the digital world? Since 1993, many have turned to Language, Culture, and Society for answers to questions like those above because of its comprehensive coverage of all critical aspects of linguistic anthropology. This seventh edition carries on the legacy while addressing some of the newer pressing and exciting challenges of the 21st century, such as issues of language and power, language ideology, and linguistic diasporas. Chapters on gender, race, and class also examine how language helps create - and is created by - identity. The seventh edition includes expanded discussions of online communication, social media outlets, and the ways the internet is changing how we interact. Coverage of race and ethnicity has also been expanded to include Latin- and Asian-American contributions to English vernacular. Enhanced and updated pedagogical features include learning objectives at the beginning of each chapter, discussion and comprehension questions at the end of each chapter, and a glossary for easy reference, making this an essential text for any course covering the evolution of language."--Page [4] of cover.
Introducing Linguistic Anthropology -- Methods of Linguistic Anthropology -- The "Nuts and Bolts" of Linguistic Anthropology I: Language Is Sound -- The "Nuts and Bolts" of Linguistic Anthropology II: Structure of Words and Sentences -- Communicating Nonverbally -- The Development and Evolution of Language: Language Birth, Language Growth, and Language Death -- Acquiring and Using Language(s): Life with First Languages, Second Languages, and More -- Language Through Time -- Languages in Variation and Languages in Contact -- The Ethnography of Communication -- Culture as Cognition, Culture as Categorization: Meaning and Language in the Conceptual World -- Language, Culture, and Thought -- Language, Identity, and Ideology I: Variations in Gender -- Language, Identity, and Ideology II: Variations in Class, "Race," Ethnicity, and Nationality -- The Linguistic Anthropology of a Globalized and Digitalized World.
JRT Cabazares (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
In English with some characters in Japanese, Greek, Cyrillic, Hebrew, Latin, Phoenician and Arabic.
Keywords: Anthropological linguistics; Language and culture; Sociolinguistics